The impact of social media influencers on the youth in Malaysia / Aida Nabilah Azman ... [et al.] - Azman, Aida Nabilah; Ridzuan, Abdul Rauf; Ab Ghani, Siti Nur Farrah Faadiah; Yahya, Fatimah Yazmin; Ramlan, Aini Faezah; Bakar, Mohd Hilmi (Faculty of Communication & Media Studies, 2022)
According to studies, millennial consumers' shopping decisions are influenced by celebrities, social media influencers, and individuals they know in real life. This study looks into how celebrities, influencers, and individual consumers know personally influence how millennials use social media information to influence the youth. Because of the ease of access and extensive usage of social media has become the ideal medium for businesses seeking to disseminate product information, generate public opinion, and acquire followers. To that aim, social media influencers serve as a dynamic third-party endorser, spreading a brand's message to a global audience. To that end, the study involves a systematic review to evaluate the various tactics used by these influencers to influence clients. According to the study's findings, these influencers significantly affect client impressions and attitudes since they are more adept at speaking to a particular sector. Compared to traditional advertising techniques, this new technology means of influencers provide the agencies with new competitive power in engaging customers and establishing brand recognition.